NK Cell-Mediated Recall Responses: Memory-Like, Adaptive, or Antigen-Specific? - Stary, Victoria; Stary, Georg (Frontiers in Cellular and Infection Microbiology, 2020)
Mounting experimental evidence hints to an import role for natural killer (NK) cells in adaptive immune responses to pathogens. NK cells with adaptive features are heterogeneous and belong to different subsets according to their phenotype as well as the nature of their adaptive recall reactions. Three types of adaptive NK cell responses have been described: (i) NK cells with long-lived memory of multiple different haptens and viral antigens were described in murine liver tissue with a possible human counterpart; (ii) infection of human and mouse cytomegalovirus is associated with an expansion of NKG2C+ and Ly49H+ NK cells, respectively, that selectively recognize CMV-encoded peptides thereby facilitating recall responses; (iii) cytokine-stimulated NK cells respond to different stimuli with enhanced production of IFN-γ after re-stimulation. These exciting findings not only support the idea of NK cells with adaptive features, but define a novel field of harnessing memory NK cell subsets for therapeutic strategies.